CONSOLIDATED FINANCIAL STATEMENTS. - Hill, Thomas M.; Dixon, Robert L.; Mautz, Robert K.; McMullen, Stewart Y.; Moonitz, Maurice; Powell, Weldon; Thorsteinson, Erlind H. (The Accounting Review, 1955)
Abstract In connection with its continuing study of the concrete meaning of "business entity," the Committee on Concepts and Standards of the American Accounting Association has selected the area of consolidated financial statements as one of importance. The basic principles of consolidated financial statements include that firstly, in the absence of special circumstances, consolidated statements are useful representations of financial position and results of operations when a dominant central financial interest in two or more companies exists and is accompanied by administrative control of their activities and resources. Secondly, in so far as practicable, the consolidated data should reflect the underlying assumption that they represent the operations, resources, and equities of a single entity. The first principle is a statement of policy, of objective, defining broadly the entity or area of consolidation, the second principle sets forth a general guide to the procedures of consolidation.